Microalbuminuria in hypertension and its relationship to target organ damage: A cross-sectional observational study in a tertiary hospital in Eastern India - Diptak Bhowmick; Sisir Chakraborty; M D Hamid Ali; Kaushik Ghosh; Amitava Acharyya; Partha Sarathi Karmakar; Swati Banerjee (Journal of Clinical and Scientific Research, 2023)
Background: Microalbuminuria (MA) is an independent risk factor in association with fatal cardiovascular and cerebrovascular outcomes among patients with hypertension (HTN). Methods: An observational study was conducted among 100 randomly selected hypertensive patients January 2013 to January 2014 to observe the proportion of MA among hypertensive patients and the proportion of presence of various target organ damages (TODs) in them. Results: The frequency of MA was 36% among participants. The frequency in males was slightly more than females (38.2% vs. 33.3%). The frequency of MA increased linearly with the duration and severity of HTN. It was more commonly found in smokers than in non-smokers. Diastolic dysfunction (42%) and Grade 2 hypertensive retinopathy (60.7%) were associated with MA. TOD was frequently observed in MA-positive patients. Conclusions: The proportion of patients with MA was in increasing trend with increasing age of hypertensive participants and duration of history of HTN. Hypertensive retinopathy, regional wall motion abnormality and neurological deficit emerged to be sensitive surrogate markers for MA in patients with HTN.